The Emergence of Orange Bonds as a Sustainable Financing Instrument: A Scoping Review and Future Research Needs - Fiesty Utami; Refi Pratiwi; Tri Wahyudi (Jurnal Riset Akuntansi, 2026)
Orange bonds are sustainable bond instruments which the funds are specifically used to finance gender equality, climate action, women's empowerment, and other social inclusion programs. This research uses the scoping review method, with the aim of systematically mapping the emergence of orange bonds and gender-responsive sustainable finance, as well as identifying publication trends, methodological approaches, research themes, and existing gaps. Searches were carried out on Web of Science, Scopus, Business Source Complete, JSTOR, and Google Scholar databases following the PRISMA-ScR protocol. Based on 2,847 initial records, 300 researches met the inclusion criteria. The research results show that although the sustainable finance literatures are expanding rapidly at 55% per year, there are only 12 studies that specifically addressed orange bonds. The most of research is quantitative econometric methods (47%), and is concentrated in East Asia (28%) and Europe (34%), while developing nations are underrepresented (<20%). Gender integration only appeared in 15% of the studies. This large research gap limits market and policy development. Based on this, the expansion of research, the development of standardized gender impact metrics, and policy harmonization to support orange bonds as a catalyst for sustainable development are absolutely necessary.